Analisis Kesalahan Berbahasa pada Daerah Kesulitan Morfologi dalam Teks Persuasi Peserta Didik Kelas VIII SMPN 2 Pameungpeuk - Nurfadhilah, Silmi Shiyam; Hidayati, R. Panca Pertiwi; Setiawan, Setiawan (Jurnal Artikula, 2021)
Language cannot be separated from a text and learning, because text is a tool for understanding a language. When learning a language, problems or mistakes are always there. Language errors can describe the abilities of students, especially in the field of morphology, namely the form of words. Errors in word formation that are not in accordance with the rules of the Indonesian language mean that the use of the language is less communicative, so that the message conveyed cannot be received properly and even misunderstandings occur. Based on the problems found, the authors are interested in conducting research with analysis techniques for language errors in part of morphological difficulty in the persuasion text created by class VIII students at SMPN 2 Pameungpeuk. The author makes several questions as a reference for research, namely: 1) What is the form of difficulty that causes affixation errors in the persuasion text made by class VIII students of SMPN 2 Pameungpeuk ?; 2) What is the form of difficulty that causes reduplication errors in the persuasion text made by class VIII students of SMPN 2 Pameungpeuk ?; 3) What is the form of difficulty that causes composition errors in persuasion texts made by class VIII students of SMPN 2 Pameungpeuk? The method used in this research is qualitative method. The data source in this study is persuasion texts made by class VIII students of SMPN 2 Pameungpeuk. Based on the results of the analysis there are several language errors in the morphological difficulty areas, including 41 affixation errors, 19 reduplication errors, and 11 composition errors. One of the causes of language errors is due to the difficulty of learning morphology students are accustomed to using everyday language rather than standard language. To improve vocabulary mastery, educators should provide new vocabulary to students, which are then applied in Indonesian language learning communication.